Reproducibility of Blood Pressure Response to the Cold Pressor Test: The GenSalt Study - Zhao, Qi (Oxford University Press, 2012)
An elevated blood pressure (BP) response to the cold pressor test (CPT) is associated with increased risk of hypertension and cardiovascular disease. However, it is still unclear whether BP response to the CPT is a stable and reproducible trait over time. Using the same study protocol, the authors repeated the CPT 4.5 years after initial administration among 568 Han Chinese in rural northern China (2003–2005 and 2008–2009). BP was measured using a standard mercury sphygmomanometer prior to and 0, 1, 2, and 4 minutes after the participants immersed their hand in ice water (3°C–5°C) for 1 minute. Absolute BP levels and BP responses during the CPT in the initial and repeated administrations were highly correlated. For example, the correlation coefficients were 0.67, 0.73, 0.71, and 0.72 for absolute systolic BP levels at 0, 1, 2, and 4 minutes after ice-water immersion (all P 's < 0.0001). The correlation coefficients for systolic BP response were 0.41 at 0 minutes, 0.37 at 1 minute, 0.42 for maximum response, and 0.39 for the area under the curve during CPT (all P 's < 0.0001). These data indicate that BP response to the CPT is a long-term reproducible and stable characteristic in the general population.